Reconstruction of Qur’anic Character Education Values through Thematic Tafsir and Its Implications for Contemporary Islamic Education - Rahmani. N (Jurnal Hadratul Madaniyah, 2026)
This study aims to reconstruct Qur’anic character education values through a thematic (maudhu‘i) tafsir approach and to formulate their implications for the development of contemporary Islamic education. This research employs a qualitative method with thematic analysis of Qur’anic verses on noble character (akhlaq al-karimah), examined through relevant classical and contemporary tafsir literature as well as modern character education studies. The findings indicate that character values such as ṣidq (honesty), ṣabr (patience), amanah (trustworthiness), tawadhu’ (humility), rahmah (compassion), responsibility, discipline, and social concern are not merely positioned as individual moral norms, but as an integral ethical system shaping the paradigm of Qur’anic education. This reconstruction affirms that character education in the Qur’an is transformative—integrating spiritual, personal, and social dimensions—and remains relevant in addressing the challenges of moral crisis and value degradation in the contemporary era. The implications suggest that these values can be formulated as a conceptual framework for developing a holistic and contextual Islamic education curriculum, emphasizing value internalization, role modeling, and habituation as primary pedagogical strategies. Unlike previous studies that tend to be descriptive-normative, this research offers a systematic thematic synthesis and an integrative conceptual model that positions Qur’anic values as the epistemological foundation for the development of contemporary Islamic character education.